Methods in Gut Microbial Ecology for Ruminants - Makkar, Harinder P.S.; McSweeney, Christopher S.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2005)
Asaresultofvarioushumanactivities,suchasincreaseinhumanpopulation,decrease in arable land due to soil degradation, urbanization, industrialization and associated increase in the demand for livestock products, dramatic changes are occurring in the global ruminant livestock sector. These changes includeshift inthesize of regional livestock populations and in the types of management and feeding systems under which ruminant livestock are held, and increased demand of a wider range of quality attributes from animal agriculture, not just of the products themselves but also of the methods used in their production. The livestock sector will need to respond to newchallengesofincreasinglivestockproductivitywhileprotectingenvironmentand human health and conservingbiodiversity and natural resources. The micro-organisms in the digestive tracts of ruminant livestock have a profound in?uence on the conversion offeedinto end products, which can impact on the- imal and theenvironment. As the livestock sector grows particularly in developing countries, there will be an increasing need to understand these processes for b- ter management and use ofbothfeed and other natural resources that underpinthe development of sustainable feeding systems.
Keywords: Zoology; Agriculture; Ecology .; Microbial ecology; Molecular ecology; Microbiology; Zoology; Agriculture; Ecology; Microbial Ecology; Molecular Ecology; Microbiology